2011
DOI: 10.1016/j.ajpath.2011.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Type I Collagen Cleavage Is Essential for Effective Fibrotic Repair after Myocardial Infarction

Abstract: Efficient deposition of type I collagen is fundamental to healing after myocardial infarction. Whether there is also a role for cleavage of type I collagen in infarct healing is unknown. To test this, we undertook coronary artery occlusion in mice with a targeted mutation (Col1a1 r/r ) that yields collagenase-resistant type I collagen. Eleven days after infarction, Col1a1 r/r mice had a lower mean arterial pressure and peak left ventricular systolic pressure, reduced ventricular systolic function, and worse di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 36 publications
1
12
0
2
Order By: Relevance
“…Another hallmark of aging is hypertension. We previously found that the blood pressure of young (<4 months) Col1a1 r/r mice was not different than that of wild-type control mice (Nong et al ., 2011 ). To determine whether differences existed with aged mice, blood pressures of 13-month-old mice were assessed using computerized tail-cuff plethysmography.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another hallmark of aging is hypertension. We previously found that the blood pressure of young (<4 months) Col1a1 r/r mice was not different than that of wild-type control mice (Nong et al ., 2011 ). To determine whether differences existed with aged mice, blood pressures of 13-month-old mice were assessed using computerized tail-cuff plethysmography.…”
Section: Resultsmentioning
confidence: 99%
“…Such interplay could have substantial consequences for the rate of vascular deterioration. Type I collagen proteolysis has been found to impact SMC adhesion and migration (Carragher et al ., 1999 ; Li et al ., 2000 ; Fera et al ., 2004 ; Nong et al ., 2011 ). Whether collagen that is resistant to cleavage affects SMC aging is not known.…”
Section: Introductionmentioning
confidence: 99%
“…To further elucidate the effect of GW1516 intervention on lesion collagen, picrosirius red-stained aortic sinus sections were imaged with circular polarization microscopy to detect fibrillar collagen 22 ( Figure 2B). The collagen area fraction of lesions was 24% in HFHC-fed animals and 31% in lesions of mice subjected to GW1516 intervention (P=0.025; Figure 2F).…”
Section: Gw1516 Attenuates Aortic Sinus Atherosclerosis and Aortic Inmentioning
confidence: 99%
“…We report here the first use of the birefringence mode of the LC-PolScope for quantitatively imaging fibrillar collagen in tissues, and comparing it against SHG microscopy. Previous studies [32,33] have used the LC-PolScope as a tool for looking at directionality of collagen fibers and alignment in collagen gels but not for quantitating collagen organization in pathology samples. This study proposes that the LC-PolScope could be a powerful tool for histopathology by measuring changes in collagen organization.…”
Section: Introductionmentioning
confidence: 99%